Clinical, Molecular, and Environmental Risk Factors for Hodgkin Lymphoma. (14th October 2010) - Maggioncalda, Alison; Malik, Neha; Shenoy, Pareen; Smith, Melody; Sinha, Rajni; Flowers, Christopher R.
Abstract : Epidemiological studies suggest unique occurrence patterns of Hodgkin lymphoma (HL) worldwide. In most Western countries there is a clear bimodal age distribution with an early peak in young adults followed by a second peak in older adults, particularly among males. In the Middle East and Asia, HL is more common in early childhood. There also are marked racial differences in the presentations of HL and HL subtypes, and particular single nucleotide polymorphisms (SNPs) have been identified as etiological factors suggesting that gene-gene and gene-environment interactions are involved. Personal health choices such as exercise and smoking may modify an individual's chances of developing HL. Numerous studies highlight the impact that exposure to Epstein-Barr virus and other environmental factors have on HL risk. Understanding the relative importance of each of these findings and their links to HL development and survival will help clinical researchers expand curative therapies and create preventative strategies for HL.